Conscience and Moral Good - Dura, Adam (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2015)
The article discusses the issue of the relationship between conscience and moral good. The main problem analysed in this paper takes the form of the following question: In what way can conscience be a moral motif for the realization of the moral good? As concluded, it is impossible to accept the hypothesis of conscience as the basis of absolute moral good. However, the negation of the important status of conscience in the realization of moral good would be an error in moral philosophy. In philosophical anthropology this would mean depriving human beings of the significant attribute of their condition.